Co-occurrence of tethered cord syndrome and cervical spine instability in hypermobile Ehlers-Danlos syndrome - Gensemer, Cortney; Daylor, Victoria; Nix, Jared; Norris, Russell A.; Patel, Sunil (Frontiers in Neurology, 2024)
The Ehlers-Danlos Syndromes (EDS) represent a group of hereditary connective tissue disorders, with the hypermobile subtype (hEDS) being the most prevalent. hEDS manifests with a diverse array of clinical symptoms and associated comorbidities spanning the musculoskeletal, neurological, gastrointestinal, cardiovascular, and immunological systems. hEDS patients may experience spinal neurological complications, including cervico-medullary symptoms arising from cranio-cervical and/or cervical instability/hypermobility, as well as tethered cord syndrome (TCS). TCS is often radiographically occult in nature, not always detectable on standard imaging and presents with lower back pain, balance issues, weakness in the lower extremities, sensory loss, and bowel or bladder dysfunction. Cervical instability due to ligament laxity can lead to headaches, vertigo, tinnitus, vision changes, syncope, radiculopathy, pain, and dysphagia. TCS and cervical instability not only share clinical features but can also co-occur in EDS patients, posing challenges in diagnostics and clinical management. We present a review of the literature and a case study of a 20-year-old female with hEDS, who underwent surgical interventions for these conditions, highlighting the challenges in diagnosing and managing these complexities and underscoring the importance of tailored treatment strategies to improve patient outcomes.